Fragranced Orchid Species from Darjeeling District of West Bengal, India: Coelogyne Flaccida Lindl. and C. Pempahisheyana Chowdhery - Yonzone, Rajendra; Lama, D.; Rai, Samuel (Indian Forester, 2014)
This article deals with availability status and taxonomic details of most fragranced two Coelogyne epiphytic Orchid species Coelogyne flaccida Lindl. and C. pempahisheyana Chowdhery from Darjeeling district of West Bengal, India. Description, date of collection, phenology, altitudinal ranges, status, local distribution and general distribution are given in detailed.bution are given in detailed.